EARLY TRIASSIC ORIGIN OF COCCOLITHOGENESIS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
Calcareous nannofossil investigations were conducted on Lower and Middle Triassic marine successions from South China. Coccoliths, nannoliths and calcispheres are relatively frequent and moderately preserved, showing an increase in diversity from the Smithian (Olenekian) to the Ladinian. The oldest nannofossils, dated to the Smithian, include Eoconusphaera hallstattensis and very simple coccoliths attributed to a sp. A morphogroup. Nannoliths of Prinsiosphaera triassica and Carnicalyxia, along with rare specimens of Tetralithus pseudotrifidus and Crucirhabdus cf. C. minutus are present in the Spathian-Pelsonian (Olenekian-Anisian) and Longobardian (Ladinian) samples, respectively. A total of 10 new morphotypes are also described. The Smithian coccoliths documented here significantly narrow the temporal gap between molecular clock estimates for the origin of calcifying coccolithophores and their first fossil record. Our data represent the oldest known nannofossils and push back the onset of coccolithophore calcification by approximately 40 million years, shortly after the end-Permian mass extinction. The Olenekian primitive, simple and tiny coccoliths from South China suggest that early coccolithophores emerged in a coastal environment of the eastern Tethys Ocean. The onset of calcification in Calcihaptophycidae may have been facilitated by suppressed atmospheric CO2 levels, coupled with increased nutrient availability following the emplacement of the Siberian Traps. The emergence of this new phytoplanktonic group correlates with the earliest recovery of benthic calcifiers, potentially shaping post-extinction marine biodiversity and influencing the evolution of the ocean toward modern conditions.
Keywords: calcareous nannofossils; Early Triassic; coccolithogenesis; South China.